THE INFLUENCE OF DISCOVERY LEARNING MODEL ON CRITICAL THINKING SKILLS OF STUDENT A: Literature Review - Sinta Wulandari; Rahmadhani Fitri; S. Syamsurizal (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2022)
The learning process in the classroom currently takes place passively because students only listen to the teacher's explanation without any question and answer interaction, students do not yet have critical thinking skills to develop their potential. Critical thinking skills are high-level thinking skills that need to be developed in schools. These skills need to be trained through the use of learning models that bring students closer to the surrounding environment to get real experiences so as to increase curiosity and explore understanding by applying the Discovery Learning learning model. This study aims to determine whether there is an influence of the Discovery Learning learning model on students' critical thinking skills. The type of research used is the literature review method in which articles are reviewed by tracing articles that are related to the topic of Discovery Learning. The results of the analysis carried out show that the Discovery Learning learning model has an influence on students' critical thinking skills.